Pengaruh Riwayat Pemberian Asi Terhadap Perkembangan Anak Usia Prasekolah Di TK Kristen Imanuel Surakarta - Lestari, Sri; AKPER Insan Husada Surakarta, Tatik Trisnowati (IJMS - Indonesian Journal on Medical Science, 2017)
Abstract: Breast milk is the most perfect food for baby. Giving breastfeeding means giving nutrition of high nutritional value that needed for growth and development of nerve and brain, giving immunity substances  to some diseases and realize the emotional bond between mother and baby. This study is a study of the correlation (correlation study) using analytical survey method with cross-sectional (cross-sectional). Analysis shows an effect of duration of breastfeeding contributes to development of children, that is   to the social development  amounted to 59.3%,  to the development of fine motor skills of children at 41.5%, on the development of childrens language to 51.9% , against gross motor development of children to 69.2%. There is a positive influence between duration of breast-feeding to the childs development, in which the childs development consists of four aspects: social personal, fine motor, language and gross motor  amounted to 78.4%. Keywords:  Breastfeeding, Child Development.  Abstrak: ASI merupakan makanan yang paling sempurna bagi bayi.Pemberian ASI berarti memberikan gizi-gizi yang bernilai gizi tinggi yang di butuhkan untuk pertumbuhan dan perkembangan saraf dan otak, memberikan zat-zat kekebalan terhadap beberapa penyakit dan mewujudkan ikatan emosional antara ibu dan bayinya. Penelitian ini merupakan penelitian studi korelasi (correlation stydy) dengan menggunakan metode survey analitik dengan rancangan cross-sectional (potong-lintang). Hasil analisis menunjukkan ada pengaruh lamanya pemberian ASI terhadap perkembangan anakyaitu terhadap perkembangan sosial sebesar 59.3%, terhadap perkembangan motorik halus anak sebesar 41.5%, terhadap perkembangan bahasa  sebesar  51.9%, terhadap perkembangan motorik kasar anak, sebesar  69.2%.Ada pengaruh positif antara lamanya pemberian ASI  terhadap perkembangan anak, dimana perkembangan anak terdiri dari 4 aspek yaitu personal sosial, motorik halus, bahasa, dan motorik kasar sebesar  78.4%.Kata kunci : Pemberian ASI, Perkembangan Anak